The ambiguous role of partially protected marine protected areas in Australia: Results from a systematic literature review - Genevieve A. C. Phillips; Emily Ogier; Ian Dutton; Neville Barrett; Nils C. Krueck; Klaas Hartmann (PLoS ONE, 2025)
Marine protected areas (MPAs) are an important tool in helping to protect biodiversity in the oceans. Recent ratification of the Kunming-Montreal Global Biodiversity Framework (GBF) has ensured that globally we are committed to effectively protecting 30% of the world’s oceans by 2030, in MPAs. In Australia there is considerable interest in the potential benefits that partially protected areas (PPAs) may provide. However, a consistent definition of a PPA is currently lacking, and urgently needed to conduct quantitative analyses of PPAs. We conducted a systematic literature review to understand the current knowledge surrounding PPAs and their potential benefits. We define a PPA, characterise PPA implementation in Australia, and present results for the outcomes of PPAs in terms of ecological, economic, and social indicators. Our review suggests that although 45% of Australia’s marine environment is within MPAs, 61% of MPAs provide only partial protection. The Northern Territory (100%), New South Wales (81%), and Queensland (79.8%) have the highest percentage of MPAs that are partially protected, compared to Tasmania which has the smallest percentage of partially protected MPAs (13.12%). Tasmania also has the smallest percentage cover of MPAs (6.49% state waters). Most PPA management plans did not contain quantifiable Key Performance Indicators (KPIs) to be able to effectively monitor the progress of these PPAs against the stated outcomes. We find the benefits of PPAs to be ambiguous: PPAs generally provide benefits when compared to ‘open’ ocean, however this is not a consistent result. There are no PPAs that provide greater overall benefits when compared to fully protected MPAs. Only one state (South Australia) and the Commonwealth (Australian Marine Parks) are collecting publicly available baseline data to facilitate quantitative monitoring of PPAs. Contrary to fisheries management, there were no plans of action if the declared MPAs and PPAs failed to meet their declared objectives and goals. Some PPAs within Australia appear to be incompatible with conservation priorities according to the recent “MPA Guide” classification framework. This study highlights the need for clearer management rationale and plans for PPAs in Australia, as these comprise the majority of MPAs in Australia’s Exclusive Economic Zone.